Respiratory Failure in Acid Maltase Deficiency - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
Sleep-disordered breathing (SDB) and respiratory failure (RF) were studied in 27 patients with juvenile and adult acid maltase deficiency (AMD) and compared with polysomnography outcomes at the University of Essen, Germany.